Methadone-Induced Polymorphic Ventricular Tachycardia Complicated by Takotsubo Cardiomyopathy in a Malnourished Patient - Mohammed Ali MD; Omeralfaroug Adam MD; Ahmed Subahi MD; Abdalaziz Awadelkarim MD; Lubna Fatiwala MD; Manmeet M. Singh MD; Rashid Alhusain MD; Randy Lieberman MD (SAGE Publishing, 2021)
Takotsubo cardiomyopathy (TC) is a syndrome characterized by acute and transient regional systolic myocardial dysfunction. TC often mimics myocardial infarction without obstructive coronary disease. We present a case of a 48-year-old woman who developed TC following the onset of polymorphic ventricular tachycardia in the setting of methadone intoxication.